Mapping Soil Erosion Sensitive Areas in Organic Matter Amended Soil Associations in the Ntabelanga area, Eastern Cape Province, South Africa - Cosmas Parwada; Johan van Tol (Journal of Applied Sciences and Environmental Management, 2020)
The study aims to map areas sensitive to erosion by water and rainfall erosivity after addition of organic matter (OM) in highly unstable soils. A soil association map was created using digital soil mapping methodology. Soil samples from six soil associations were incubated and analysed for several soil erodibility measures and inferred to the soil association map. Soil stabilization against soil erosion by use of OM was evaluated for 30 weeks under two simulated rainstorms, intermittent rainstorms (IR) and single rainstorm (SR). Rainfall erosivity (R-factor) was calculated from the duration of a rainstorm and the total amount of rainfall received under rainfall simulations. Erodibility factor (K-factor) was estimated using the soil OM content and texture. Largest area (40%) was covered by shallow soils and K-factor range of 0.0693-0.0778 t.ha.hha-1MJ-1mm-1. Largest (60.2%) area had a structural stability index of 0.8 and 42.7% of the area was covered by a dispersion ratio value range of 0.65-0.70. The area size with erosion rates of > 15 t/ha/yr was drastically reduced from 1 to 8 weeks after OM application thereafter gradually increased under both IR and SR.  Soil erosion rates of < 5 t-1 ha-1 yr-1 and > 15 t-1 ha-1 yr-1 were most and least observed respectively under both storms. R-factor was higher under IR than SR and the smallest areas with soil erosion rates of > 15 t-1 ha-1 yr-1 contributed most to the lost soil. Organic matter confers soil resistance to erosion up to a certain period before losing its effectiveness. The study provided first assessment of erosion dynamics, basis for identifying  conservation priorities which may be applicable in similar areas.